Induced mandibular condylar growth in a sheep model after functional appliance treatment - Ma Bingkui; Sampson Wayne; Fazzalari Nicola; Wilson David; Wiebkin Ole (Sciendo, 2001)
This paper reports on changes in mandibular condylar growth in sheep fitted with experimental functional appliances. The paper also addresses the similarities of mandibular condylar growth in sheep and humans. Experimental functional appliances were developed, constructed and applied to four, four-month old, male sheep. Another four sheep served as matched controls. All animals received fluorochrome bone labels during the study and their weight gain also was recorded. Fifteen weeks later, all animals were sacrificed and each temporo-mandibular joint and left metacarpus were removed. Undecalcified mid-sagittal sections of the joint and metacarpus were prepared for fluorescence microscopy. The mandibular condylar growth vector in sheep was found to be in a postero-superior direction. Condylar growth in the control sheep during the experimental period varied from 8.8 to 11.9 mm, with the mean being 10.6 mm, which is quantitatively similar to two years of condylar growth in human adolescents. In the experimental sheep, the condylar growth varied from 8.5 to 13.3 mm, with the mean being 11.4 mm. When metacarpal growth and weight gain were taken into consideration using multivariant analysis, the coefficients for growth in the postero-superior and posterior direction were found to be high, with adjusted r2 as 0.84 and 0.82 respectively. The induced condylar growth was estimated to be largest in the posterior direction (2.30 mm), which is also similar to previous reports in humans. These findings suggest the appropriateness of using sheep as a model for quantitative histological analysis when investigating the mechanisms of functional appliance treatment.